Exploring Agenda Diversity in European Public Service Media Sports Desks: A Comparative Study of Underrepresented Disciplines, Sportswomen and Disabled Athletes' Coverage on Twitter. (25th January 2021) - Rojas-Torrijos, José Luis; Ramon, Xavier
ABSTRACT: In the digital age, many people are concerned about how Public Service Media (PSM) will be able to fulfill their remits and promote "cultural citizenship" through sports journalism. Delivering diverse content should be a cornerstone of PSM in their myriad platforms: they should not only concentrate on mainstream disciplines but also give exposure to underrepresented sports, leagues, and individuals, and organizations including female athletes and athletes with disabilities. This article employs a content analysis to explore sports agenda diversity on Twitter in four European PSM: RTVE (Spain), FranceTV (France), RAI (Italy), and RTÉ (Ireland). The examination of more than 7000 tweets over a 3-month period reveals that the long-standing inequalities with regard to sports diversity, gender and disability are reinforced, rather than counteracted, in the current landscape. In short, social media platforms seem to perpetuate a fairly restricted and routinized agenda. Going forward, PSM should take advantage of the potential of social media to promote a diverse and multi-faceted menu that ultimately contributes to enhance "cultural citizenship."